PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Novi Nurcahyani (LAND JOURNAL, 2026)
This study aims to analyze the effect of profitability, firm size, and firm growth on firm value with capital structure as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange during 2019–2024. The research employed a quantitative approach using purposive sampling, resulting in 60 companies as the sample with a total of 360 observations. Data were analyzed using panel regression with EViews 13. The findings indicate that profitability and firm size have a significant effect on firm value, while firm growth has no significant effect. Capital structure significantly affects firm value and mediates the relationship between firm size and firm value, but does not mediate the relationship between profitability or firm growth and firm value. Simultaneously, profitability, firm size, and firm growth significantly influence firm value. These results highlight the importance of optimal capital structure management and asset efficiency in enhancing firm value and provide practical implications for investors in conducting fundamental analysis.